The Influence of Parental Guidance, Group of Peers, School Promotion, and Career Information on Course Preference Decision Class X SMK Muhammadiyah in Bantul - Pujilestari, Siska; Sayuti, Muhammad; Tentama, Fatwa (Journal of Vocational Education Studies, 2021)
The purpose of the study was to analyze the influence of parental guidance, peer group, school promotion, and career information on course preference decision. This study applied a mixed-method with quantitative (multiple regression) followed by the qualitative stage. The quantitative analysis technique is done by a regression test and continued with qualitative. The results showed that partially and simultaneously, the variables of parental guidance, peer groups, school promotion, and career information affected the decision making in choosing the competency of students of SMK Muhammadiyah in Bantul. Career information factors of 12.98% most influence students' decision making in choosing expertise competencies. School promotion contributed 8.20% of the decision. The peer factor contributes to 4.78% of the students’ choices. The last of these factors was parental guidance, which provided 4.43%.